Natural History of Idiosyncratic Drug-Induced Liver Injury and Prognostic Models - Devarbhavi, Harshad; Andrade-Bellido, Raúl Jesús (Wiley, 2025)
Background and Aims: Drug-induced liver injury (DILI) remains a leading cause of acute liver failure worldwide. Drugs such as isoniazid, alone or in combination with other anti-tuberculosis drugs, as well as a growing number of herbal and complementary medicines, have been implicated in most cases of acute liver failure in registry studies. Methods: This review summarizes current knowdledge on the acute and chronic outcomes in patients with idiosyncratic DILI and discusses several of the existing prognostic models. Results and Conclusions: The reasons why some individuals progress from DILI to end-stage liver disease are still largely unknown. However, collaborative efforts over the past few decades have provided figures on the relative incidence of drug-induced acute liver failure and allowed the development of prognostic models to predict this worse outcome at the onset of the event. The outcome of chronic DILI is less well characterised due to the lack of sufficient follow-up in cohort studies, but several phenotypes of DILI can progress to chronicity, and specific drugs such as nitrofurantoin or amiodarone are classic examples of agents leading to chronic forms of DILI. Therapy for drug-induced acute liver failure and chronic DILI is mainly supportive, although some randomised clinical trials have shown beneficial effects of N-acetylcysteine and corticosteroids.
Keywords: Hígado - Enfermedades; Pronóstico médico; Chronic DILI; Corticosteroids; Drug-induced acute liver failure; Prognostic factors